Comparison of performance using Daubechies Wavelet family for facial expression recognition - M., Satiyan; M., Hariharan; Ramachandran, Nagarajan, Prof. Dr. (Institute of Electrical and Electronics Engineers (IEEE), 2010)
Link to publisher's homepage at http://ieeexplore.ieee.org/